A Nurse‐Led Limited Risk Factor Modification Program to Address Obesity and Obstructive Sleep Apnea in Atrial Fibrillation Patients. Issue 23 (4th December 2018) - Yaeger, Amaryah; Cash, Nancy R.; Parham, Tara; Frankel, David S.; Deo, Rajat; Schaller, Robert D.; Santangeli, Pasquale; Nazarian, Saman; Supple, Gregory E.; Arkles, Jeffrey; Riley, Michael P.; Garcia, Fermin C.; et al.
Abstract : Background: Obesity and obstructive sleep apnea (OSA) are associated with atrial fibrillation (AF), yet these conditions remain inadequately treated. We report on the feasibility and efficacy of a nurse‐led risk factor modification program utilizing a pragmatic approach to address obesity and OSA in AF patients. Methods and Results: AF patients with obesity (body mass index ≥30 kg/m 2 ) and/or the need for OSA management (high risk per Berlin Questionnaire or untreated OSA) were voluntarily enrolled for risk factor modification, which comprised patient education, lifestyle modification, coordination with specialists, and longitudinal management. Weight loss and OSA treatment were monitored by monthly follow‐up calls and/or continuous positive airway pressure (CPAP) unit downloads. Quality of life and arrhythmia symptoms were assessed with the SF‐36 and AF Severity Scale at baseline and at 6 months. From November 1, 2016 to October 31, 2017, 252 patients (age 63±11 years; 71% male; 57% paroxysmal AF) were enrolled, 189 for obesity and 93 for OSA. Obese patients who enrolled lost significantly greater percent body weight than those who declined (3% versus 0.3%; P <0.05). Among 93 patients enrolled for OSA, 70 completed sleep studies, OSA was confirmed in 50, and the majority (76%) started CPAP therapy. All components of quality of life and arrhythmia symptoms improved significantly from baseline to 6 months among enrolled patients. Conclusions: A nurse‐led risk factor modification program is a potentially sustainable and generalizable model that can improve weight loss and OSA in AF patients, translating into improved quality of life and arrhythmia symptoms.